JavaScript Primer plus: enhancing Web pages with JavaScript Programming Language - Torok, G; Payne, J; Westfield, M (International journal of information management, 1998)
Book review abstract. Waite Group Press, Corte Madera, California: 1996, 588pp., $39.99. ISBN 1-57169-041-7. Reviewed by A. G. Kelly.